Strategi Penguatan Moderasi Beragama Pada Sekolah Dasar - Muhammad Alwan; Husairi Husairi; Muhammad Munir (Alifbata : Jurnal Pendidikan Dasar, 2024)
So the purpose of this study is to describe a rigid strategy in providing reinforcement of religious moderation values to elementary school children. Especially how to integrate the values of religious moderation, especially in the teaching and learning process. This research uses a descriptive qualitative approach, where in obtaining data is carried out by library research through various literature that has been filtered according to the topic to be discussed. Furthermore, data collection techniques are carried out by reducing data, presenting data, and drawing conclusions. The results of the study show that starategy that can be done in strengthening religious moderation is by internalizing the value of Bergama moderation in the curriculum, compiling material by inserting religious moderation, good role models, problem-based learning strategies, cooperative learning and so on.